(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The aim of the study is to investigate the difference inpersonality characteristics of the pupils of rural and urban groups. The randomsample of 200 boys in which 100 were rural and 100 urban were selected fromsecondary schools of Hisar tehsil (Dist: Hisar), age ranged from 11 to 15years. The Children’s Personality Questionnaire (CPQ) was used to measurepersonality characteristics. Means and SDs were computed and‘t’ test wasapplied to check the significance of the difference between personalitystructure of the two groups. The findings indicate that the urban group is morewarm & sociable, more intelligent, more emotionally stable and moreenthusiastic, while the rural group is more excitable and less practical andrealistic and more dependent. Out of fourteen factors of CPQ the factor E, G,H, J, N, Q3 and Q4 demonstrated insignificant differences.